Kinship analysis and allelic dropout: a forensic approach on an archaeological case - Sara Palomo-Díez; Ángel Esparza Arroyo; Mirian Tirado-Vizcaíno; Javier Velasco Vázquez; Ana María López-Parra; Cláudia Gomes; Carlos Baeza-Richer; Eduardo Arroyo-Pardo (Taylor & Francis Group, 2018)
Background: This study relies on the discovery of two pit burials (LTA and LTB) of the Bronze Age Cogotas I archaeological culture (circa 3600-2950 BP) in Spain. LTA was a single burial and LTB contained three skeletal remains of two adults and a newborn or foetus at term. Aim: The central question posed by this find was whether the LTB tomb constituted a traditional nuclear family (father, mother and son or daughter). Methods: Ancient and forensic DNA protocols were employed to obtain reliable results. Autosomal, X-STR markers and mitochondrial DNA were amplified. Subsequently, different kinship probabilities were estimated by means of LR values calculated using the Familias 3 software. Furthermore, an allelic dropout sensitivity test was developed in order to evaluate the influence of allelic dropout phenomena on the results. Results: It was possible to determine the molecular sex of all individuals and to establish a maternal relationship between the perinatal individual and one of the adults. Conclusion: The remains in the LTB tomb were not a traditional nuclear family (father, mother and son/daughter) and it was probably a tomb where two women, one of them pregnant, were buried.